Evaluation of a new patient consultation initiative in community pharmacy for ear, nose and throat and eye conditions - Gillian Hall; Tania Cork; Simon White; Hayley Berry; Louise Smith (BMC, 2019)
Abstract Background Community pharmacy Common Ailments Services can ease the considerable workload pressures on primary and secondary care services. However, evidence is needed to determine whether there are benefits of extending such services beyond their typically limited scope. This study therefore aimed to evaluate a new community pharmacy model of a service for patients with ear, nose and throat (ENT) and eye conditions who would otherwise have had to seek primary care appointments or emergency care. Methods People with specified ENT or eye conditions registered with General Practitioners in Staffordshire or Shropshire who presented at participating community pharmacies were offered a consultation with a pharmacist trained to provide the service. The service included provision of relevant self-care advice and, where clinically appropriate, supply of non-prescription medicines or specified prescription-only medicines (POMs), including antibiotics, under Patient Group Directions. Patients received a follow up telephone call from the pharmacist five days later. Data were collected on the characteristics of patients accessing the service, the proportion of those who were treated by the pharmacist without subsequently seeing another health professional about the same condition, and patient reported satisfaction from a questionnaire survey. Results A total of 408 patients accessed the service, of whom 61% received a POM, 15% received advice and medicine supplied under the common ailments service, 9% received advice and purchased a medicine, 10% received advice only and 5% were referred onwards. Sore throat accounted for 45% of diagnoses where a POM was supplied, 32% were diagnosed with acute otitis media and 15% were diagnosed with acute bacterial conjunctivitis. The number of patients successfully followed up was 309 (76%), of whom 264 (85%) had not seen another health professional for the same symptoms, whilst 45 (15%) had seen another health professional, usually their GP. The questionnaire was completed by 259 patients (response rate 63%) of whom 96% reported being very satisfied or satisfied with the service. Conclusions The study demonstrates that pharmacists can effectively diagnose and treat these conditions, with a high degree of patient satisfaction. Wider adoption of such service models could substantially benefit primary care and emergency care services.